2002
DOI: 10.1021/jp014234w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen-Bonded Intermediates in the Bimolecular Reactions of the Hydroxyl Radical

Abstract: Because of their importance in atmospheric and combustion chemistry, the rate coefficients and mechanisms of gas-phase reactions of the OH radical have been studied extensively, and the kinetic database for these reactions is unsurpassed. The OH radical has a rather large electric dipole moment (1.668 D) and is clearly capable of forming strong hydrogen bonds. In this article, we examine the evidence for the importance of such interactions in reactions of OH. We propose that the reactions of OH with alkanes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
237
3
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(249 citation statements)
references
References 67 publications
7
237
3
1
Order By: Relevance
“…Accordingly, the binary OH-H 2 O complex has been extensively studied by theoretical and experimental methods. 31,40,88,93,94,96 This complex was observed and investigated by gas phase microwave spectroscopy. 93,96 Infrared spectra were obtained in rare gas matrices leading to agreement as to the global minimum geometry which features a hydrogen bond between the hydrogen of OH and the oxygen in H 2 O.…”
Section: Bimolecular Reactions In Water Complexesmentioning
confidence: 99%
“…Accordingly, the binary OH-H 2 O complex has been extensively studied by theoretical and experimental methods. 31,40,88,93,94,96 This complex was observed and investigated by gas phase microwave spectroscopy. 93,96 Infrared spectra were obtained in rare gas matrices leading to agreement as to the global minimum geometry which features a hydrogen bond between the hydrogen of OH and the oxygen in H 2 O.…”
Section: Bimolecular Reactions In Water Complexesmentioning
confidence: 99%
“…Weakly bound complexes have also been invoked to explain rate coefficients that increase as the temperature is lowered [7]. Electronic structure calculations by Xu and Lin [8] for the reaction between OH and methanol have shown the presence of a weakly-bound (~ 20 kJ mol -1 ) hydrogen-bonded complex prior to the barrier to reaction, as shown in Figure 1.…”
mentioning
confidence: 99%
“…Kinetic studies have shown that the OH ϩ HONO 2 reaction is unusual in several respects (3,(5)(6)(7)(8)(9)(10)(11), particularly under the temperature and pressure conditions found in the lower atmosphere. Under these conditions, this reaction exhibits a negative temperature dependence, a pressure dependence, and a strong kinetic isotope effect.…”
mentioning
confidence: 99%